A hybrid statistical modelling, normalization and inferencing techniques of an off-line signature verification system - Ahmad S.M.S.; Shakil A.; Faudzi M.A.; Anwar R.Md.; Balbed M.A.M. (2023)
This paper presents an automatic off-line signature verification system that is built using several statistical techniques .The learning phase involves the use of Hidden Markov Modelling (HMM) technique to build a reference model for each local feature extracted from a set of signature samples of a particular user. The verification phase uses three layers of statistical techniques.. The first layer involves the computation of the HMM-based log-likelihood probability match score. The second layer performs the mapping of this score into soft boundary ranges of acceptance or rejection through the use of z-score analysis and normalization function. Next Bayesian inference technique is used to arrive at the final decision of accepting or rejecting a given signature sample. 2008 IEEE.